A core outcome set for clinical trials of chemoradiotherapy interventions for anal cancer (CORMAC): a patient and health-care professional consensus. (December 2018) - Fish, Rebecca; Sanders, Caroline; Adams, Richard; Brewer, Julie; Brookes, Sara T; DeNardo, Jill; Kochhar, Rohit; Saunders, Mark P; Sebag-Montefiore, David; Williamson, Paula R; Renehan, Andrew G
Summary: Chemoradiotherapy is the primary treatment for patients with squamous cell carcinoma of the anus, but variations in the reported outcomes have restricted between-study comparisons. Treatment-related morbidity is considerable; however, no trial has comprehensively quantified long-term side-effects or quality of life. Therefore, we established the first international health-care professional and patient consensus to develop a core outcome set, using the Core Outcome Measures in Effectiveness Trials method. We used the results from our previous systematic review and combined them in this Review with patient interviews to derive a comprehensive list of outcomes, followed by a two-round Delphi survey completed by 149 participants (55 patients and 94 health-care professionals) from 11 countries. The Delphi results were discussed at a consensus meeting of health-care professionals and patients. Agreement was reached on 19 outcomes across four domains: disease activity, survival, toxicity, and life impact. Implementation of the Core Outcome Research Measures in Anal Cancer (CORMAC) set in future trials will serve as a framework to achieve standardisation, facilitate selection of health-area-specific evaluation tools, reduce redundancy of outcome lists, allow between-study comparisons, and ultimately enhance the relevance of trial findings to health-care professionals, trialists, and patients.